Tutorials in Endovascular Neurosurgery and Interventional Neuroradiology - Byrne, James Vincent (Springer International Publishing : Imprint: Springer, 2017)
The new edition of this book updates an established text written for trainees and practicing endovascular therapists. The content is based on the curriculum of the Endovascular Neurosurgery MSc degree course at Oxford University and its tutorial system of teaching. The tutorial is a learning episode focused on a particular topic. The book is presented as a series of tutorials, which introduces and guides students through background literature, highlights relevant research data, and provides insights on treatments from an experienced practitioner. Each tutorial covers a different topic to provide a complete review of the subspecialty and its theoretical basis. It is intended to equip the reader with a foundation of knowledge on which to build their clinical practice and a reference base for further study. Its practical approach to endovascular therapy will help the reader to understand recent developments in this rapidly expanding field of medicine.